The Stele of Adad-nērārī III and Nergal-ēreš from Dūr-Katlimmu (Tell Šaiḫ Ḥamad) - Radner, Karen (2012)
A Neo-Assyrian royal stele from Dūr-Katlimmu, modern Tell Šaiḫ Ḥamad in Syria, bears two cuneiform inscriptions, one in the name of Adad-nērārī III of Assyria (r. 810–783 BC), the other in the name of Nergal-ēreš, governor of the Assyrian province of Raṣappa. Both inscriptions concern the god Salmānu and his temple at Dūr-Katlimmu for whose reconstruction and refurbishment Adad-nērārī and Nergal-ēreš take credit.
Keywords: Neo-Assyrian inscription; Dūr-Katlimmu (city); Nergal-ēreš (official); Adad-nērārī III (king); Lycian